Genome sequence and comparative pathogenomics analysis of a Salmonella enterica Serovar Typhi strain associated with a typhoid carrier in Malaysia - Yap, Kien Pong; Gan, Han Ming; Teh, Cindy Shuan Ju; Baddam, Ramani; Chai, Lay Ching; Kumar, Narender; Tiruvayipati, Suma Avasthi; Ahmed, Niyaz; Thong, Kwai Lin (American Society for Microbiology, 2012)
Salmonella enterica serovar Typhi is a human pathogen that causes typhoid fever predominantly in developing countries. In this article, we describe the whole genome sequence of the S. Typhi strain CR0044 isolated from a typhoid fever carrier in Kelantan, Malaysia. These data will further enhance the understanding of its host persistence and adaptive mechanism.